2019
DOI: 10.1002/14651858.cd013315
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing high altitude illness: Part 3. Miscellaneous and non-pharmacological interventions

Abstract: Analysis 2.2. Comparison 2 Group 2. Ginkgo biloba versus placebo, Outcome 2 Risk of high altitude pulmonary oedema........... Analysis 2.3. Comparison 2 Group 2. Ginkgo biloba versus placebo, Outcome 3 Risk of high altitude cerebral oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Beidleman et all reported that staging at 2200 m for 6 days before ascending to 4300 m reduced the incidence and severity of AMS 21 . Although a 2019 Cochrane review reported that the effect of preacclimatisation strategies on improving the risk of AMS as uncertain, it is still sensible recommending gradual ascent according to the results of the studies and extensive clinical experiences 22 . Travelers are recommended to spend 6–7 days at moderate altitude like 2200–3000 m before proceeding higher altitude.…”
Section: Preventionmentioning
confidence: 99%
“…Beidleman et all reported that staging at 2200 m for 6 days before ascending to 4300 m reduced the incidence and severity of AMS 21 . Although a 2019 Cochrane review reported that the effect of preacclimatisation strategies on improving the risk of AMS as uncertain, it is still sensible recommending gradual ascent according to the results of the studies and extensive clinical experiences 22 . Travelers are recommended to spend 6–7 days at moderate altitude like 2200–3000 m before proceeding higher altitude.…”
Section: Preventionmentioning
confidence: 99%
“…Some pharmacological interventions ( e.g., acetazolamide) have been shown to reduce AMS symptoms [10, 11]. However, a recent Cochrane review concluded that there is currently no clear evidence for any non-pharmacological intervention to robustly mitigate AMS [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some pharmacological interventions (e.g., acetazolamide) have been shown to reduce AMS symptoms [10,11]. However, a recent Cochrane review concluded that there is currently no clear evidence for any nonpharmacological intervention to robustly mitigate AMS [12]. Interestingly, early studies in rodents observed that increasing ketone bodies (KB) in the blood improved tolerance to extreme hypoxia (FIO2: 4-5%) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The Wilderness Medical Society has released recommendations for the prevention of AMS, including gradual ascent and taking acetazolamide and/or dexamethasone (Luks et al, 2019). However, some persons do not ascend gradually, and some cannot tolerate the side effects of the drugs, although intolerance to acetazolamide is rare; therefore, new nonpharmacological approaches still need to be explored (Bartsch & Swenson, 2013; Molano Franco, Nieto Estrada, Gonzalez Garay, Marti‐Carvajal, & Arevalo‐Rodriguez, 2019).…”
Section: Introductionmentioning
confidence: 99%